Qur'an - E. H. Palmer, tr.; Muller, F. Max, ed. (Delhi Low Price, 1995)
Contents: pt.II. (vi, 362 p).
Library has part II only
Includes index
Keywords: Oriental literature -- Translations into English; Sacred books